ENDOSCOPIC BILIARY STENT THERAPY - N. ÖRMECİ and A. DÖKMECİ and S. KARAYALÇIN and K. BAHAR and A. R. BEYLER and H. M. SÖKMEN and N. SİPAHİ and; ZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-